Extraction and characterization of phytochemical compounds from araçazeiro (Psidium cattleianum) leaf: Putative antioxidant and antimicrobial properties. (November 2020) - Zandoná, Giovana Paula; Bagatini, Lucíola; Woloszyn, Natália; de Souza Cardoso, Juliane; Hoffmann, Jessica Fernanda; Moroni, Liziane Schittler; Stefanello, Francieli Moro; Junges, Alexander; Rombaldi, Cesar Valmor
Graphical abstract: Highlights: Pressurized liquid extracts of araçá leaf have a greater number of compounds. The extracts are rich in phenolic compounds. All extracts showed antioxidant activity. The tested extracts were more effective against Gram-positive bacteria. Abstract: Underexplored species have phytochemical potential for pharmacological and nutraceutical applications. The fruits of such species, including aracá ( Psidium cattleianum Sabine), are rich in specialized metabolites with putative antioxidant and antimicrobial activity; therefore, the leaves of these species are also a potential source of bioactive compounds. In this study, araçazeiro leaves were extracted using an aqueous infusion (Al) and a pressurized liquid extraction system with water (PLE-W), ethanol (PLE-E), and 1:1 water:ethanol ratio combination (PLE-W:E). PLE-W:E yielded a greater diversity of extracted compounds. Nonetheless, all extracts showed inhibitory activity against pathogenic Gram-positive and Gram-negative bacteria and antioxidant activity in the in vitro thiobarbituric acid reactive substances (TBARS) and reactive oxygen species (ROS) assays with rat brain and yeast model systems. Thus, araçazeiro leaves can be exploited as a promising source of bioactive compounds.